Protective Effect of Nigella Sativa Oil Against Indomethacin-Related Small Intestine and Gastric Mucosal Damage in Rats - VELİOĞLU ÖĞÜNÇ, AYLİZ; ÇETİNEL, ŞULE (AVES, 2021)
BACKGROUND/AIMS The aim of this study was to investigate the effects of Nigella sativa (NS) oil form on reducing the damage caused by indomethacin in the stomach and duodenum of rats owing to their antioxidant and anti-inflammatory properties. MATERIAL and METHODS The rats were divided into 4 groups: group 1, saline-treated control group; group 2, NS-treated control group; group 3, saline-treated ulcer group and ulcers caused by indomethacin (30 mg/kg) and administration of physiological serum; group 4, NS-treated ulcer group, which is the group receiving NS oil after administration of indomethacin. At the end of the study, blood samples collected from animals were examined for tumor necrosis factor alpha (TNF-alpha), interleukin-1 beta (IL-1 beta), and glutathione (GSH), malondialdehyde (MDA) levels and myeloperoxidase (MPO),and Na+/K+-ATPase activities in gastric and intestinal tissue samples. RESULTS Levels of TNF-alpha and IL-1 beta in serum and MDA and MPO values in tissue were found to be higher in the saline-treated ulcer group than in the saline-treated control group. In addition, tissue GSH and Na+/K+-ATPase levels were found to be lower. These values were found to be reversed when comparing NS-treated ulcer group to saline-treated ulcer group. Histopathological findings showed epithelial regeneration and improvement instead of dense tissue damage. CONCLUSION The strong antioxidant and anti-inflammatory effects of NS against potential small intestine and gastric damage were shown using an experimental indomethacin-induced ulcer model in rats. Hence, our study suggests that NS used together with indomethacin can prevent gastrointestinal damage; thus, this agent can create a new clinical therapeutic principle.
Keywords: Indomethacin; Nigella sativa oil; ulcer; glutathione; INJURY; THYMOQUINONE; EXTRACT; ULCER